Critical incidents triggering physician managers’ sensemaking of their meaning at work - SLIM , Hiba; GARREAU, Lionel (Proche-Orient Études en management, 2023)
This study is to explore the way physician managers make sense of their work. Through interviews with 25 physician managers from different managerial levels working in different hospitals across Lebanon, we underlie the influence of critical incidents on their meaning at work. The recalled incidents encountered by the interviewed physician managers throughout their management journey revolved around five main themes: healthcare industry constraints, organizational challenges, negative job characteristics, relationship problems with subordinates and peers, and unmet expectations. The findings revealed important aspects influencing the attraction and development of future physician managers.